The Islamic world and Japan : (Th Japan Foundation, 1981)
Since 1975, the Japan Foundation has sponsored an international symposium every year, focussing particulary on cultural exchange bewwen Japan and the development countries. The sixth in this series of meetings, the "Islamic civilization and Japan", was help in Tokyo from march 21 to March 29, 1980. It was hoped that these meetings would broaden the achievements of the "International symposium: Cultural bases of Mutual Understanding between the middle East and Japan" help in 1977, the proceedings of that earlier symposium, dialogue: middle East and Japan, have already been published.